Young in class: Implications for inattentive/hyperactive behaviour of Canadian boys and girls. (December 2015) - Chen, Kelly; Fortin, Nicole; Phipps, Shelley
Abstract: Using data from the Statistics Canada National Longitudinal Survey of Children and Youth (NLSCY), this paper investigates the impact of school entry age on inattentive/hyperactive behaviours. We employ both an across‐provinces and time difference‐in‐differences approach and a within‐province regression discontinuity design. We find that being young in class causes greater inattentive/hyperactive behaviour, exacerbating any inattentive/hyperactive behaviour exhibited prior to school entry. These results also hold in sibling fixed effect models. We do not find gender differences in the effects, although since boys are more likely to be inattentive/hyperactive at school entry, they are more affected. These effects persist into early adolescence.